Implementasi Algoritma Ripemd160 Untuk Mendeteksi Keaslian Sertifikat Tanah - Joslin Nababan; Pristiwanto Pristiwanto; M Sayuthi (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
In this era, land certificates are often used as collateral to apply for loan money, both directly and online, so the security of land certificates needs to be improved. Land certificates in digital form, the manipulation process is very easy. Today there is a lot of software that can be used to manipulate digital images. With the sophistication of the software it can make manipulated digital images difficult for humans to know directly. The process of manipulation of digital data is also easy to do, so it needs a mechanism to know that a digital certificate, does not change from the original. In cryptography, there are various methods that can be used to secure a data, both to maintain the confidentiality of the data, and detect the authenticity of the data. One technique that can be used is the hash function in cryptography. The hash function is a one-way function that can be used to determine the authentication of a message. To ensure an original document or not, there are several methods with the concept of authentication, and can detect document changes from the results of manipulation, one of which is the RIPEMD160 algorithm. Applying the RIPEMD160 algorithm will make it easier and faster to detect the authenticity of digital images.Keywords: cryptography, Hash Function, RIPEMD160